(untitled) (Journal of Scientific Research, 2022)
In this study, an efficient Agrobacterium-mediated genetic transformation method followed by Tc chitiI gene for enhanced expression in peanut (Arachis hypogaea L.) cv ICG 7827 is reported. A. tumefaciens strain LBA 4404 harboring the plant transformation plasmid pBinAR contains the Tc chitI gene and nptII gene as a selectable marker. The precultured leaflet (LL) explants were infected with A. tumefaciens containing Tc chitiI gene and cocultivated on SIM (MMS+10 mg/L BAP+1 mg/L NAA+2 mg/L AgNO3) for four days. After co-cultivation, these explants were transferred to selection medium (SIM+75 mg/L Kan+250 mg/L Cefotaxime). In T0 generation, 70 % of transformation efficiency was recorded. T1 generation derived from the primary transgenic (T0) events revealed a Mendelian inheritance pattern (3:1) for the Tc chit I transgene. T1 transgenic peanut plants were tested for resistance against C. arachidicola, C. personatum, and P. arachidis by infection with the microspores using detached leaf assay. The Tc chitI gene expressed in T1 transgenic plants have shown longer incubation, longer latent period, and lower infection frequencies than non-transformed (WT) plants. A significant negative correlation was recorded between chitinase activity and the frequency of infection to the C. arachidicola, C. personatum and P. arachidis pathogens.